2013
DOI: 10.1007/s12098-013-1163-z
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion in Sickle Cell Disease: Experience from a Gujarat Centre

Abstract: Transfusion usage greatly exceeds that in the Jamaican Sickle Cell Clinic. Transfusion therapy carries risks and cost and more detailed investigation and diagnosis of anemic episodes is necessary to define the role of transfusion among other potential therapies. Eventually, guidelines evolved by Indian specialists should determine the indications for transfusion in sickle cell disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…However, a study by V. Mehta et al in 2013 reported frequency of transfusions was 5.2%. 10 In this study, frequency of HbSS genotype patients reported 74.57%. Similar study reported by Hassan M et al in 2003 frequency of HbSS 88% 1.…”
Section: Aim and Objectivesmentioning
confidence: 54%
“…However, a study by V. Mehta et al in 2013 reported frequency of transfusions was 5.2%. 10 In this study, frequency of HbSS genotype patients reported 74.57%. Similar study reported by Hassan M et al in 2003 frequency of HbSS 88% 1.…”
Section: Aim and Objectivesmentioning
confidence: 54%
“…The African forms of sickle cell disease have more severe features than those with the Asian haplotype where frequent alpha thalassemia and persistence of HbF may protect against some of the serious early pathologies of the disease. More information is needed on the Asian haplotype, 117 before the role of transfusion can be determined in that population, and transfusion in the steady state 118 requires justification. As the Asian haplotype of SS disease becomes better documented and understood, the role of transfusion therapy in its management will be more readily defined.…”
Section: Resultsmentioning
confidence: 99%
“…The development of models of care appropriate to societies with high frequencies of variant haemoglobins and limited resources has made the Jamaican experience of value to other societies. As a result, the Jamaican experience has been sought by colleagues in Brazil, Greece (119), Turkey, Saudi Arabia (120-122), Bahrain, Uganda (123,124) and India (125)(126)(127)(128)(129), and has also contributed to the development of sickle cell care in more developed countries such as the USA and the UK. These collaborations have also provided research opportunities for learning about the variability of sickle cell disease and the determinants of this variability.…”
Section: Geographic Comparisonsmentioning
confidence: 99%